Penerapan Metode 3R (Reuse, Reduse, Recycle) dalam Pengelolaan Limbah Domestik dan B3 untuk Meningkatkan Status Proper Hijau di PT.XYZ - Mukti, Anggoro Daru; Purba, Humiras Hardi (Universitas Suryakancana, 2022)
In increasing production and manufacturing processes at PT. XYZ will certainly have an impact on the PT. XYZ as well as for residents around the PT. XYZ from the activity process. Currently PT. XYZ is committed to environmental management by participating in government programs, namely from the Ministry of Environment and Forestry such as PROPER. currently the PROPER rating of PT. XYZ is still getting the blue title in the near future PT. XYZ is committed to increasing the blue rating to become the Green PROPER title as a form of improving the quality of environmental management. One aspect of the Green PROPER assessment from the Ministry of Environment and Forestry is in accordance with the company's roadmap with an implementation plan in 2022-2023. Aspects that are reviewed and planned include: Waste management by Method 3 R (Reduce, Reuse, Recyle) at PT. XYZ B3 waste management using the 3 R (Reduce, Reuse, Recyle) method at PT. XYZ. From the results of the study and data obtained in the field, PT. XYZ produces domestic waste or waste of about ±348 Kg/day with a total number of 580 employees and B3 waste produced ±200 Kg/day. Domestic organic and inorganic waste / waste is made into compost, magot and inorganic materials into handicrafts. B3 waste specifically for sludge from the WWTP process can be processed into paving blocks and bricks. Reducing the use of TL lamps replaced with LED lamps. One strategy for reducing B3 waste, namely electronic waste generated and energy savings using environmentally friendly LED lights, can save energy by ± 15% and reduce B3 waste by ± 10%. This 3R method can be used as a sustainable environmental management program or a green industry. To get a green PROPER rating or report card that is included in the points in the DRKPL Dalam peningkatan produksi dan proses manufaktur di PT. XYZ tentunya akan menimbulkan dampak bagi lingkungan Pabrik PT. XYZ maupun bagi warga sekitar pabrik PT. XYZ dari proses kegiatan tersebut. Saat ini PT. XYZ berkomitmen dalam pengelolaan lingkungan salah satu dengan keikutsertaan dalam program pemerintah yaitu dari KLHK seperti PROPER. saat ini peringkat PROPER PT. XYZ masih memperoleh predikat biru dalam waktu dekat ini PT. XYZ berkomitmen untuk meningkatkan predikat biru menjadi predikat PROPER Hijau sebagai bentuk peningkatan kualitas pengelolaan lingkungan. Salah Satu aspek penilaian PROPER Hijau dari KLHK sesuai dengan roadmap perusahaan dengan rencana implementasi pada tahun 2022-2023.Aspek yang di kaji dan direncanakan meliputi :Pengelolaan sampah dengan Metode 3R (Reduce,Reuse, Recyle) di PT.XYZ Pengelolaan limbah B3 dengan Metode 3 R (Reduce,Reuse, Recyle) di PT.XYZ. Dari hasil kajian dan data yang didapat di lapangan PT.XYZ menghasilkan sampah atau limbah domestik sekitar ±348 Kg/hari dengan jumlah total karyawan 580 orang dan limbah B3 yang dihasilkan ±200 Kg/hari. Limbah /Sampah domestik organik dan anorganik dibuat menjadi kompos, magot dan anorganik menjadi kerajinan tangan. Limbah B3 khusus untuk lumpur dari sis proses IPAL dapat diolah menjadi paving block dan batako. Pengurangan penggunaan lampu TL diganti menjadi lampu LED sebagai. Salah satu strategi pengurangan limbah B3 yaitu limbah elektronik yang dihasilkan dan penghematan energi menggunakan lampu LED yang ramah lingkungan dapat mengefisienkan energi sebesar ± 15% dan menurunkan pengeluaran limbah B3 sebanyak ± 10%.metode 3R ini bisa dijadikan program pengelolaan lingkungan berkelanjutan atau green industry. Untuk memperoleh peringkat atau raport PROPER hijau yang masuk dalam point di dalam DRKPL.